2019
DOI: 10.1016/j.yebeh.2019.01.045
|View full text |Cite
|
Sign up to set email alerts
|

The direct cost of seizure events in severe childhood-onset epilepsies: A retrospective claims-based analysis

Abstract: Objective: The objective of the study was to assess the direct cost of medically treated seizure events in severe childhood-onset epilepsies. Lennox-Gastaut syndrome (LGS), Dravet syndrome (DS), and tuberous sclerosis complex (TSC) are representative conditions associated with frequent intractable seizures. Methods: Commercial and Medicaid insurance claims from 2010 to 2015 were queried to identify patients with possible LGS, possible DS, or TSC, having ≥2 years of continuous insurance from the date of first e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 25 publications
4
42
0
Order By: Relevance
“…Our findings agree with previously published analyses that the healthcare costs associated with LGS are significant [6,11,13]. All previous studies note that the mean annual costs associated with probable LGS are very high; where the comparison has been shown, these costs exceed those of patients without LGS (Appendix Table S2), and also exceed those of other encephalopathies such as DS and TSC [14]. In the present study, the largest component of direct healthcare costs was inpatient care (33%).…”
Section: All Patientssupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings agree with previously published analyses that the healthcare costs associated with LGS are significant [6,11,13]. All previous studies note that the mean annual costs associated with probable LGS are very high; where the comparison has been shown, these costs exceed those of patients without LGS (Appendix Table S2), and also exceed those of other encephalopathies such as DS and TSC [14]. In the present study, the largest component of direct healthcare costs was inpatient care (33%).…”
Section: All Patientssupporting
confidence: 93%
“…Since all previous studies have used an algorithm to detect the patients most likely to have been diagnosed with LGS, all studies refer to patients with 'probable LGS'. The algorithm used was highly consistent between these studies [6,11,13,14]. As noted previously, LGS is a predominantly childhood-onset syndrome, most commonly manifesting itself between ages 3-5 years [4], yet no previous study has included a maximum age cut-off for the first diagnosis of epilepsy as an indicator for probable LGS.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent 3-month retrospective questionnaire study revealed substantial direct and indirect healthcare costs associated with TSC in Germany [32]. Two previous studies have reported high healthcare costs specifically for individuals with TSC and epilepsy, although neither analysis compared costs for those with and without epilepsy [12,13]. Authors of a study based on the UK CPRD concluded that the high costs incurred by individuals with TSC and epilepsy are likely to reflect the diverse and severe TSC-related manifestation profile of the individuals, since having 2 or more TSC manifestations was found to be a significant cost driver [13].…”
Section: Tablementioning
confidence: 99%
“…Despite the frequent occurrence of epilepsy with TSC, few studies have focused specifically on burden of illness in this population, suggesting a need for further data. Two of the available studies have reported direct healthcare costs related to TSC and epilepsy in the USA [12] and UK [13], while several other studies have assessed healthcare resource utilisation and/or medication use [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%